(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: The Mini-Clinical Evaluation Exercise (Mini-CEX) is a valuable formative assessment tool in medical education. It involves direct observation of a student’s clinical skills by a faculty member, followed by immediate constructive feedback. There is limited data available on the utility of Mini-CEX for undergraduate assessment. The aim of this study was to compare the effectiveness and reception of Mini-CEX and traditional practical assessments in Pediatrics among medical students and faculty members. Materials and Methods: This prospective educational comparative study was conducted over six months, from April 2021 to September 2021, involving undergraduate medical students of Phase-3, Part-2. The students were randomly divided into four groups (A, B, C, and D). In the first encounter, two groups participated in a traditional practical examination, while the other two groups underwent a Mini-Clinical Evaluation Exercise (Mini-CEX) assessment. For the second encounter, the assessment methods were swapped between the two groups. Systematic feedback was provided to each student following the Mini-CEX assessment. Additionally, feedback was collected from both, students and faculty members, regarding their experiences and opinions on the assessment methods. Results: This study found that Mini-CEX scores were significantly higher than TPE scores (P=0.006489). There was also significant inter-examiner variability in Mini-CEX marks (p < 0.00001). Both students and faculty members provided positive feedback regarding the Mini-CEX. Despite its benefits, the time required to conduct the examination is a major limitation for undergraduate assessment. Conclusions: Mini-CEX is a valuable tool in undergraduate medical education for assessing and improving clinical skills. By providing structured, real-time feedback, it helps students develop into competent and confident clinicians. The time required to conduct the examination is a major limitation for undergraduate assessment.